High-superelasticity high-temperature shape memory alloy microwire with temperature of over 500 DEG C and preparation method thereof
By adjusting the element content and adding B and Ce elements on the basis of Ni50Mn25Ga25, the existing high-temperature shape memory alloys have been solved, and high-temperature shape memory alloy microfilaments with large superelastic strain and excellent cyclic stability are achieved.
Patent Information
- Application Number
- CN202510131260.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-18
AI Technical Summary
The existing high-temperature shape memory alloys exhibit small superelastic strain, poor cyclic stability and high cost in service environments above 500°C, which limits their wide application in aerospace and other fields.
Based on Ni50Mn25Ga25, the Ni atomic content is increased, the Mn and Ga content is reduced, and trace amounts of B and Ce elements are added. By increasing the average valence electron number of the material and increasing the lattice distortion, the phase transition temperature of the alloy and the super-elastic resilience strain are increased.
Large super elastic high-temperature shape memory alloy microfilaments above 500℃ have been obtained, which have excellent super elasticity and cycle stability, low cost, and are suitable for high-temperature applications.
Smart Images

Figure CN119843108A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sensors and intelligent materials and preparation thereof, and specifically relates to a superelastic high-temperature shape memory alloy microwire above 500°C and a preparation method thereof. Background Art
[0002] With the rapid development of aerospace, automobile, energy exploration, mechanical electronics and other industries, especially the urgent demand for high-temperature sensing and driving materials in the fields of aircraft engines, fire protection devices, current overload protection and nuclear reactors, high-temperature shape memory alloys (martensitic phase transition starting temperature) as new intelligent sensing and driving materials are becoming more and more popular. M s High temperature shape memory alloys (higher than 100°C) are considered to be the key materials for solving major problems in the above fields. The common problems faced by existing high temperature shape memory alloys are that the service temperature is not high enough (no more than 400°C), the high temperature superelastic strain is small (less than 5%), the cycle stability is poor and the cost is high, so that the existing high temperature shape memory alloys can only be used in certain key fields, and their widespread use is limited. Therefore, the development of high temperature shape memory alloys with large superelastic strain, excellent cycle stability and low cost at 400°C or even above 500°C has become an important breakthrough in promoting the development of high-tech fields such as aerospace.
[0003] Among the existing high-temperature shape memory alloy systems, Ti-Ni-(Pt / Pd / Au / Hf) shape memory alloy is currently the most promising type of high-temperature shape memory alloy. However, since this type of alloy contains a large amount of rare and precious metal elements such as Pt, Pd, Au or Hf, its raw material cost is relatively high, and the superelastic strain of this type of alloy is usually less than 5%. In addition, at higher temperatures, especially above 400°C, the processes of phase decomposition, dislocation movement and creep (or recovery and recrystallization) in this type of alloy are more active, resulting in a rapid increase in residual strain, a significant decrease in recoverable strain, and poor cyclic stability, which makes it difficult to be widely used in service environments above 400°C and under conditions with high cost requirements. Therefore, it is urgent to develop a low-cost alternative material for high-temperature shape memory alloys with better performance.
[0004] In addition to high response frequency and large output strain under magnetic field, Ni-Mn-Ga shape memory alloy also has the characteristics of high phase transition temperature, easy adjustment and low alloy cost. As a high-temperature shape memory alloy, it has been widely studied and paid attention to in the past two decades. Ni-Mn-Ga shape memory alloy single crystal has the properties of large superelastic strain (up to 10%) and high service temperature (up to 400℃). However, the preparation process of single crystal is complicated, time-consuming, high production cost, and difficult to scale production, making it difficult to put it into industrial production and enter the practical stage. In contrast, the preparation of polycrystalline Ni-Mn-Ga shape memory alloy is relatively simple, and the preparation cost and energy consumption are low. However, the presence of a large number of grain boundaries in polycrystalline alloys will lead to its high brittleness and unsatisfactory functional behavior, which has become one of the important reasons restricting the high-temperature application of polycrystalline Ni-Mn-Ga shape memory alloy.
[0005] In recent years, memory alloy wires with large superelasticity can be widely used in thermal sensors, driver components, earthquake damping and textile fabrics. They are intelligent materials that integrate sensing and driving. At present, some scholars have used glass coating method to prepare Ni-Mn-Ga based shape memory alloy microwires, and obtained excellent superelasticity and large recoverable strain below 400℃. However, after exceeding 400℃, the microwires have obvious residual strain during unloading, and it is difficult to obtain large superelasticity at higher temperatures (such as 500℃), so its high temperature application is limited.
[0006] Therefore, there is a need for a superelastic high-temperature shape memory alloy microwire having a temperature above 500°C and a preparation method thereof. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a superelastic high temperature shape memory alloy microwire with a temperature above 500°C in view of the above-mentioned shortcomings of the prior art. 50 Mn 25 Ga 25 On this basis, the content of Ni atoms with higher valence electron number is increased, and the content of Mn atoms and Ga atoms with lower valence electron concentration is reduced, so as to increase the average valence electron number of the material to increase the phase transition temperature. At the same time, by adding trace non-metallic B elements and rare earth Ce elements with smaller atomic radius, superelastic high-temperature shape memory alloy microwires with a temperature of more than 500°C are obtained.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a superelastic high temperature shape memory alloy microwire with a temperature above 500°C, characterized in that the molecular formula of the superelastic high temperature shape memory alloy microwire is: (Ni a Mn b Ga c ) 100-x-y B x Ce y, where a, b, c, x, and y represent the atomic percentage values of the corresponding elements.
[0009] The above-mentioned superelastic high-temperature shape memory alloy microwire at above 500°C is characterized in that the (Ni a Mn b Ga c ) 100-x-y B x Ce y In the equation, a is 53~57, b is 20~24, c is 19~23, x is 0.1~0.9, y is 0.05~0.5, and a+b+c=100.
[0010] The superelastic high temperature shape memory alloy microwire of the present invention is a 50 Mn 25 Ga 25 On this basis, the content of Ni atoms with higher valence electron number (valence electron number is 10) is increased, and the content of Mn atoms (valence electron number is 7) and Ga atoms (valence electron number is 3) with lower valence electron concentration is reduced. The phase transition temperature of the alloy is increased by increasing the average valence electron number of the material. On this basis, a trace amount of non-metal B (atomic radius is smaller than Ni, Mn, and Ga) and rare earth Ce (atomic radius is larger than Ni, Mn, and Ga) are added at the same time, and the lattice distortion of the alloy is increased by co-doping of the two elements, changing the austenite and martensite The lattice parameters of the body are increased, the theoretical transformation strain is increased, and the superelastic recoverable strain of the alloy at high temperature is improved. In addition, excessive B elements and Ce elements are dissolved in the matrix, causing large lattice distortion, which further increases the superelastic recoverable strain of the alloy at high temperature. The large lattice distortion causes the vacancy gap at the grain boundary to be larger than that inside the crystal. The B element fills the vacancy at the grain boundary, reduces the grain boundary energy, improves the grain boundary cohesion and creep resistance, slows down the processes of phase decomposition and dislocation movement at high temperature, reduces the irrecoverable strain value, and finally obtains superelastic high-temperature shape memory alloy microwires above 500℃.
[0011] The above-mentioned superelastic high-temperature shape memory alloy microwire with a temperature above 500°C is characterized in that the superelastic high-temperature shape memory alloy microwire still has superelasticity at a temperature of 530°C, the recoverable strain is not less than 9.5%, and the non-recoverable strain is not more than 0.1%.
[0012] In addition, the present invention also provides a method for preparing a superelastic high-temperature shape memory alloy microwire at a temperature above 500°C, characterized in that the method comprises the following steps: Step 1, melting the master alloy: weighing single element Ni and single element Mn with an atomic ratio of 2:3-8, and placing them in a vacuum suspension melting furnace for vacuum suspension melting to obtain a nickel-manganese master alloy, then grinding off the surface oxide scale, measuring the specific composition of the nickel-manganese master alloy, and finally cutting them into small pieces to obtain small pieces of nickel-manganese master alloy; Step 2: Mix the small piece of nickel-manganese master alloy obtained in step 1 with single element Ni, single element Ga, single element B and single element Ce according to (Ni a Mn b Ga c ) 100-x-y B x Ce y batching to obtain a mixed material; Step 3, melting the master alloy: placing the mixture obtained in step 2 into a vacuum non-consumable arc melting furnace for vacuum arc melting to obtain a master alloy button ingot; Step 4, suction casting: grinding the oxide scale and cleaning the master alloy button ingot obtained in step 3, then cutting it into small pieces, placing it in a vacuum arc melting furnace for suction casting, and obtaining an alloy rod with a diameter of 4 mm to 6 mm; Step 5: Prepare alloy cylinders: grind and clean the surface of the alloy rod obtained in step 4, and then cut it into small alloy cylinders with a length of 4 mm to 6 mm; Step 6, induction heating: Place the small alloy cylinder obtained in step 5 into the bottom of a high borosilicate glass test tube, then place the test tube into a conical induction coil and fix it, then turn on the power of the induction coil to heat the small alloy cylinder, so that it is completely melted and drives the bottom of the glass test tube to soften; Step 7, wire drawing: when the bottom of the glass test tube in step 6 is completely softened, use tweezers with an insulating layer to clamp the bottom of the glass test tube, pull out the composite wire material with the alloy liquid completely covered by glass, and quickly cool the composite wire material through cooling water to obtain glass-covered alloy microwires; Step 8: Remove the glass: Use fine sandpaper to gently polish the glass-coated alloy microwire obtained in step 7 to remove the surface glass, and polish it section by section until the glass is completely removed to obtain a superelastic high-temperature shape memory alloy microwire with a temperature above 500°C.
[0013] The present invention first prepares a nickel-manganese master alloy by vacuum suspension smelting, removes the surface oxide skin and measures the actual composition of the nickel-manganese master alloy, and applies it as a manganese source to subsequent arc smelting of a master alloy button ingot. The nickel-manganese is prepared according to the actual composition of the master alloy instead of directly using single substance manganese particles, which can ensure that the manganese element reaches the actual required mass and avoid volatilization during the smelting process caused by directly using single substance manganese, effectively reducing the composition deviation of the manganese content in the master alloy button ingot, making the composition of the master alloy button ingot closer to the nominal composition, and greatly improving the repeatability of the smelting process; by placing the master alloy button ingot in a vacuum arc smelting furnace for vacuum arc smelting and performing overturning smelting and multiple electromagnetic stirring, a master alloy button ingot with uniform composition is obtained, wherein even if the current is increased and the number of smelting times is increased for melting single substance B with a higher melting point, the influence on the content of manganese in the final composition is almost negligible; by After the oxide skin is polished, the purity of the alloy is improved, which is conducive to the later preparation of large superelastic high-temperature shape memory alloy microwires with higher purity. The microwires are then cut into small pieces and placed in a vacuum arc melting furnace with a suction casting device for suction casting into alloy rods. The alloy rods are cut into small cylinders and placed in a high borosilicate glass test tube for induction heating until they are completely melted and drawn. The rapid quenching process in the glass-coated wire drawing process is used to dissolve excess B elements and Ce elements in the matrix, causing large lattice distortion, further improving the superelastic recoverable strain of the alloy at high temperature, and obtaining glass-coated large superelastic high-temperature shape memory alloy microwires. Fine sandpaper is used to gently polish and gradually remove the glass on the surface of the microwires. Compared with the previous method of removing glass using hydrofluoric acid, the deglassing method used in the present invention is simpler, safer, and has lower cost, and does not require waste liquid treatment and other processes, so it is also more environmentally friendly, and finally obtains large superelastic high-temperature shape memory alloy microwires above 500°C.
[0014] The above method is characterized in that the purity of the single Ni and single Mn in step 1 and the single Ni, single Ga, single B and single Ce in step 2 is not less than 99.9%. The present invention uses raw materials with higher purity to obtain large superelastic high temperature shape memory alloy microwires with excellent performance.
[0015] The above method is characterized in that during the vacuum suspension melting process in step 1, the vacuum degree is less than 5×10 -3 Pa, the melting temperature is 1400℃~1500℃, and the melting is kept for 5min~15min after complete melting, and the melting is turned over for 3 times. The present invention adopts a higher vacuum degree to avoid oxidation of raw materials during the melting process, selects a moderate melting temperature to avoid serious volatilization of manganese elements due to excessively high melting temperature, selects a shorter insulation time to avoid volatilization of manganese elements due to long-term high temperature insulation, and melts three times by turning over to ensure uniform composition of the nickel-manganese intermediate alloy.
[0016] The above method is characterized in that before the vacuum arc melting in step 3, the furnace is first evacuated to a pressure lower than 3×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and evacuate the furnace for the second time until the pressure in the furnace is less than 3×10 -3 Pa, and then fill with argon gas again until the pressure in the furnace is -0.05MPa, and finally melt the titanium ingot to further remove the oxygen in the furnace. The present invention selects a higher vacuum degree and gas washing (two vacuumings and two argon fillings) and melts the titanium ingot to remove the oxygen in the furnace, all in order to remove the oxygen in the furnace cavity as much as possible, avoid metal oxidation during the smelting process, and ensure the quality of the large superelastic high temperature shape memory alloy microwire.
[0017] The above method is characterized in that, during the vacuum arc melting process in step 3, the melting current is 250A~320A, and the melting is turned over 5 times, wherein electromagnetic stirring is added for 30s~45s during the second, third and fourth melting processes. The present invention uses a larger melting current and turns over the melting 5 times, wherein the middle 3 times are with electromagnetic stirring, all of which are to fully melt the B single substance with a higher melting point (melting point is 2076°C) and evenly distribute it in the alloy ingot, thereby ensuring the uniformity of each component in the large superelastic high temperature shape memory alloy microwire.
[0018] The above method is characterized in that before the suction casting in step 4, the furnace is first vacuumed to a pressure lower than 3×10 - 3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and finally melt the titanium ingot to further remove the oxygen in the furnace. The present invention selects a higher vacuum degree and gas washing and melts the titanium ingot to remove the oxygen in the furnace, all in order to remove the oxygen in the furnace cavity as much as possible, avoid metal oxidation during the smelting process, and ensure the quality of the large superelastic high temperature shape memory alloy microwire.
[0019] Compared with the prior art, the present invention has the following advantages: 1. The present invention is in Ni 50 Mn 25 Ga 25 On this basis, the content of Ni atoms with higher valence electron number is increased, and the content of Mn atoms and Ga atoms with lower valence electron concentration is reduced, so as to increase the average valence electron number of the material to increase the phase transition temperature. At the same time, by adding a small amount of non-metallic B elements and rare earth Ce elements with smaller atomic radius, superelastic high-temperature shape memory alloy microwires with a temperature of more than 500°C are obtained.
[0020] 2. The present invention utilizes the rapid quenching process in the glass-coated wire drawing process to dissolve excess B elements and Ce elements in the matrix, further changing the lattice parameters of austenite and martensite, increasing the theoretical transformation strain, and improving the recoverable strain of the alloy at high temperature. In addition, large lattice distortion causes the vacancy gaps at the grain boundaries to be larger than those inside the crystal, and the B element fills the vacancies at the grain boundaries, reducing the grain boundary energy, improving the grain boundary cohesion and creep resistance, slowing down the processes of phase decomposition and dislocation movement at high temperature, reducing the irrecoverable strain value, and finally obtaining superelastic high-temperature shape memory alloy microwires above 500°C.
[0021] 3. The present invention uses fine sandpaper to gently polish and gradually remove the glass on the surface of the microwire. Compared with the previous method of using hydrofluoric acid to remove glass, the glass removal method used in the present invention is simpler, safer, and has lower cost. It also does not require waste liquid treatment and other processes, so it is also more environmentally friendly.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning image of the superelastic high-temperature shape memory alloy microwire above 500°C prepared in Example 1 of the present invention.
[0024] Figure 2 This is the X-ray diffraction pattern of the superelastic high-temperature shape memory alloy microwire above 500°C prepared in Example 1 of the present invention.
[0025] Figure 3 This is the endothermic-exothermic diagram of the superelastic high-temperature shape memory alloy microwire at above 500°C prepared in Example 1 of the present invention during the heating-cooling process.
[0026] Figure 4 This is the stress-strain curve of the 500°C or higher superelastic high temperature shape memory alloy microwire prepared in Example 1 of the present invention at 510°C.
[0027] Figure 5 This is an endothermic-exothermic diagram of the shape memory alloy microwire prepared in Comparative Example 1 of the present invention during the heating-cooling process.
[0028] Figure 6 The stress-strain curve of the shape memory alloy microwire prepared in Comparative Example 1 of the present invention at 480°C.
[0029] Figure 7 This is the stress-strain curve of the 500°C or higher superelastic high temperature shape memory alloy microwire prepared in Example 2 of the present invention at 530°C. DETAILED DESCRIPTION
[0030] Example 1 The molecular formula of the superelastic high temperature shape memory alloy microwire above 500°C in this embodiment is (Ni 55.5 Mn 23.5 Ga 21 ) 99.65 B 0.3 Ce 0.05 .
[0031] This embodiment includes the following steps: Step 1: Melting the master alloy: weigh the elemental Ni and elemental Mn with a mass purity of not less than 99.95% and an atomic ratio of 2:3, and put them into a vacuum suspension melting furnace at a vacuum degree of 4×10 -3 Pa, the melting temperature is 1400℃, and after being completely melted, it is kept warm for 15min, and the melting is turned over 3 times to obtain a nickel-manganese master alloy, and then the surface oxide scale is polished off, and the specific composition of the nickel-manganese master alloy is measured, and finally it is cut into small pieces to obtain a small nickel-manganese master alloy; Step 2: Mix the small piece of nickel-manganese master alloy obtained in step 1 with single element Ni, single element Ga, single element B and single element Ce with a purity of not less than 99.95%, according to (Ni 55.5 Mn 23.5 Ga 21 ) 99.65 B 0.3 Ce 0.05 batching to obtain a mixed material; Step 3: Melting the master alloy: Place the mixture obtained in step 2 into a vacuum non-consumable arc melting furnace and evacuate the furnace to a pressure of 2×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and evacuate the furnace for the second time until the pressure in the furnace is 2×10 -3 Pa, argon gas is filled again until the pressure in the furnace is -0.05MPa, and finally the titanium ingot is melted to further remove the oxygen in the furnace, with a melting current of 250A~320A, and the melting is turned over for 5 times, wherein electromagnetic stirring is added for 30s~45s during the second, third and fourth melting processes, and vacuum arc melting is performed to obtain a master alloy button ingot; Step 4: Suction casting: Grind the master alloy button ingot obtained in step 3, remove the oxide scale and clean it, then cut it into small pieces and put it into a vacuum arc melting furnace. First, evacuate the furnace to a pressure of 2×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, finally melt the titanium ingot to further remove the oxygen in the furnace, and then perform suction casting to obtain an alloy rod with a diameter of 4mm; Step 5: Prepare alloy cylinders: grind and clean the surface of the alloy rod obtained in step 4, and then cut it into small alloy cylinders with a length of 6 mm; Step 6, induction heating: Place the small alloy cylinder obtained in step 5 into the bottom of a high borosilicate glass test tube, then place the test tube into a conical induction coil and fix it, then turn on the power of the induction coil to heat the small alloy cylinder, so that it is completely melted and drives the bottom of the glass test tube to soften; Step 7, wire drawing: when the bottom of the glass test tube in step 6 is completely softened, use tweezers with an insulating layer to clamp the bottom of the glass test tube, pull out the composite wire material with the alloy liquid completely covered by glass, and quickly cool the composite wire material through cooling water to obtain glass-covered alloy microwires; Step 8: Remove the glass: Use fine sandpaper to gently polish the glass-coated alloy microwire obtained in step 7 to remove the surface glass, and polish it section by section until the glass is completely removed to obtain a superelastic high-temperature shape memory alloy microwire with a temperature above 500°C.
[0032] The large superelastic high-temperature shape memory alloy microwire prepared in this embodiment was subjected to microstructure observation, phase structure analysis, phase transition temperature test and high-temperature superelasticity (stress-strain curve under loading / unloading) test, and the microstructure of the microwire was observed using a field emission scanning electron microscope (SEM). Figure 1 The results showed that the surface was relatively smooth and the diameter of the microwire was about 50 μm. The room temperature phase structure of the microwire was analyzed by X-ray diffractometer (XRD). Figure 2 The results show that the microwire has a dual-phase structure at room temperature, including a tetragonal martensite phase and a face-centered cubic precipitation phase. The phase transition temperature of the microwire during the heating and cooling process was measured using a differential scanning calorimeter (DSC). Figure 3 The results show that the martensitic transformation start temperature, end temperature, austenitic transformation start temperature and end temperature of the microwire are all much higher than 100℃, indicating that the microwire belongs to the category of high-temperature shape memory alloys; the stress-strain curve of the microwire during loading and unloading at high temperature is measured by dynamic mechanical properties tester (DMA). Figure 4 The results show that the superelastic high-temperature shape memory alloy microwires prepared in this embodiment have excellent superelasticity at 510°C, with a recoverable strain of about 14% and a non-recoverable strain of less than 0.2%. It can be concluded that the best performance of the superelastic high-temperature shape memory alloy microwires prepared in this embodiment is: the recoverable strain at 510°C is 14%, and the non-recoverable strain is less than 0.2%.
[0033] Comparative Example 1 The molecular formula of the shape memory alloy microwire in this comparative example is Ni 55.5 Mn 23.5 Ga 21 .
[0034] The difference between this comparative example and Example 1 is that in step 2, elemental B and elemental Ce are not added.
[0035] The shape memory alloy microwires prepared in this comparative example were subjected to microstructure observation, phase structure analysis, phase transition temperature test and superelasticity (stress-strain curve under loading / unloading) test. The microstructure of the microwires was observed using a field emission scanning electron microscope (SEM), and the results showed that the surface of the microwires was relatively smooth and the diameter was about 65 μm. The room temperature phase structure of the microwires was analyzed using an X-ray diffractometer (XRD), and the results showed that the microwires had a dual-phase structure at room temperature, including a tetragonal martensite phase and a face-centered cubic precipitation phase. The phase transition temperature of the microwires during the heating and cooling process was measured using a differential scanning calorimeter (DSC), as shown in FIG. Figure 5 The results show that the martensitic transformation starting temperature, the end temperature, the austenitic transformation starting temperature and the end temperature of the microwire are all much higher than 100℃, indicating that the microwire belongs to the category of shape memory alloys; the stress-strain curve of the microwire during the loading and unloading process is measured by a dynamic mechanical properties tester (DMA). Figure 6 The results show that the large superelastic high-temperature shape memory alloy microwire prepared in this comparative example has superelasticity at 480°C, with a recoverable strain of 8.93% and an irrecoverable strain of 0.84%, which cannot achieve the large superelastic performance above 500°C.
[0036] By comparing Example 1 with Comparative Example 1, it can be seen that compared with Comparative Example 1 in which neither B element nor rare earth Ce element is added, Example 1 adopts the co-addition of B and Ce, which increases the lattice distortion of the microwire, changes the lattice parameters of austenite and martensite of the large superelastic high temperature shape memory alloy microwire, increases the recoverable strain of the microwire (from 8.9% to 14.0%), and reduces the irrecoverable strain value of the microwire (from 0.84% to below 0.2%), increases the maximum temperature at which the large superelastic high temperature shape memory alloy microwire produces superelasticity (from 480°C to 510°C), thereby improving the high-temperature superelasticity of the large superelastic high temperature shape memory alloy microwire.
[0037] Example 2 The molecular formula of the superelastic high temperature shape memory alloy microwire above 500°C in this embodiment is (Ni 55.5 Mn 23.5 Ga 21 ) 99.55 B 0.3 Ce 0.15 .
[0038] This embodiment includes the following steps: Step 1: Melting the master alloy: weigh the elemental Ni and elemental Mn with a mass purity of not less than 99.99% and an atomic ratio of 2:8, and place them in a vacuum suspension melting furnace at a vacuum degree of 3.5×10 -3Pa, the melting temperature is 1500℃, and after being completely melted, it is kept warm for 5 minutes, and the melting is turned over 3 times to obtain a nickel-manganese master alloy, and then the surface oxide scale is polished off, and the specific composition of the nickel-manganese master alloy is measured, and finally it is cut into small pieces to obtain a small nickel-manganese master alloy; Step 2: Mix the small piece of nickel-manganese master alloy obtained in step 1 with single element Ni, single element Ga, single element B and single element Ce with a purity of not less than 99.99%, according to (Ni 55.5 Mn 23.5 Ga 21 ) 99.55 B 0.3 Ce 0.15 batching to obtain a mixed material; Step 3: Melting the master alloy: Place the mixture obtained in step 2 into a vacuum non-consumable arc melting furnace and evacuate the furnace to a pressure of 2.8×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and evacuate the furnace for the second time until the pressure in the furnace is 2.8×10 -3 Pa, argon gas is filled again until the pressure in the furnace is -0.05MPa, and finally the titanium ingot is melted to further remove the oxygen in the furnace, with a melting current of 250A~320A, and the melting is turned over for 5 times, wherein electromagnetic stirring is added for 30s~45s during the second, third and fourth melting processes, and vacuum arc melting is performed to obtain a master alloy button ingot; Step 4: Suction casting: Grind the master alloy button ingot obtained in step 3, remove the oxide scale and clean it, then cut it into small pieces and put it into a vacuum arc melting furnace. First, evacuate the furnace to a pressure of 2.8×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and finally melt the titanium ingot to further remove the oxygen in the furnace, and then perform suction casting to obtain an alloy rod with a diameter of 6mm; Step 5: Prepare alloy cylinders: grind and clean the surface of the alloy rod obtained in step 4, and then cut it into small alloy cylinders with a length of 4 mm; Step 6, induction heating: Place the small alloy cylinder obtained in step 5 into the bottom of a high borosilicate glass test tube, then place the test tube into a conical induction coil and fix it, then turn on the power of the induction coil to heat the small alloy cylinder, so that it is completely melted and drives the bottom of the glass test tube to soften; Step 7, wire drawing: when the bottom of the glass test tube in step 6 is completely softened, use tweezers with an insulating layer to clamp the bottom of the glass test tube, pull out the composite wire material with the alloy liquid completely covered by glass, and quickly cool the composite wire material through cooling water to obtain glass-covered alloy microwires; Step 8: Remove the glass: Use fine sandpaper to gently polish the glass-coated alloy microwire obtained in step 7 to remove the surface glass, and polish it section by section until the glass is completely removed to obtain a superelastic high-temperature shape memory alloy microwire with a temperature above 500°C.
[0039] The large superelastic high-temperature shape memory alloy microwire prepared in this embodiment was subjected to microstructure observation, phase structure analysis, phase transition temperature test and high-temperature superelasticity (stress-strain curve under loading / unloading) test. The microstructure of the microwire was observed using a field emission scanning electron microscope (SEM), and the results showed that the surface was relatively smooth and the diameter of the microwire was about 70 μm. The room temperature phase structure of the microwire was analyzed using an X-ray diffractometer (XRD), and the results showed that the microwire was a two-phase structure at room temperature, including a tetragonal martensite phase and a face-centered cubic precipitation phase. The phase transition temperature of the microwire during the heating and cooling process was measured using a differential scanning calorimeter (DSC), and the results showed that the martensite phase transition start temperature, termination temperature, austenite phase transition start temperature and termination temperature of the microwire were all much higher than 100°C, indicating that the microwire belongs to the category of high-temperature shape memory alloys. The stress-strain curve of the microwire during loading and unloading at high temperature was measured using a dynamic mechanical properties tester (DMA), see Figure 7 The results show that the high-temperature shape memory alloy microwire with large superelasticity above 500°C prepared in this embodiment has excellent superelasticity at 530°C, with a recoverable strain of 9.5% and a non-recoverable strain of less than 0.1% (negligible).
[0040] Example 3 The molecular formula of the superelastic high temperature shape memory alloy microwire above 500°C in this embodiment is (Ni 53 Mn 24 Ga 23 ) 99.40 B 0.1 Ce 0.5 .
[0041] This embodiment includes the following steps: Step 1: Melting the master alloy: weigh the elemental Ni and elemental Mn with a mass purity of not less than 99.97% and an atomic ratio of 2:5, and put them into a vacuum suspension melting furnace at a vacuum degree of 3×10 -3 Pa, the melting temperature is 1450℃, and after being completely melted, it is kept warm for 10min, and the melting is turned over 3 times to obtain a nickel-manganese master alloy, and then the surface oxide scale is polished off, and the specific composition of the nickel-manganese master alloy is measured, and finally it is cut into small pieces to obtain a small nickel-manganese master alloy; Step 2: Mix the small piece of nickel-manganese master alloy obtained in step 1 with single element Ni, single element Ga, single element B and single element Ce with a purity of not less than 99.97%, according to (Ni 53 Mn 24 Ga23 ) 99.40 B 0.1 Ce 0.5 batching to obtain a mixed material; Step 3: Melting the master alloy: Place the mixture obtained in step 2 into a vacuum non-consumable arc melting furnace and evacuate the furnace to a pressure of 2.5×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and evacuate the furnace for the second time until the pressure in the furnace is 2.5×10 -3 Pa, argon gas is filled again until the pressure in the furnace is -0.05MPa, and finally the titanium ingot is melted to further remove the oxygen in the furnace, with a melting current of 250A~320A, and the melting is turned over for 5 times, wherein electromagnetic stirring is added for 30s~45s during the second, third and fourth melting processes, and vacuum arc melting is performed to obtain a master alloy button ingot; Step 4: Suction casting: Grind the master alloy button ingot obtained in step 3, remove the oxide scale and clean it, then cut it into small pieces and put it into a vacuum arc melting furnace. First, evacuate the furnace to a pressure of 2.5×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, finally melt the titanium ingot to further remove the oxygen in the furnace, and then perform suction casting to obtain an alloy rod with a diameter of 5mm; Step 5: Prepare alloy cylinders: grind and clean the surface of the alloy rod obtained in step 4, and then cut it into small alloy cylinders with a length of 5 mm; Step 6, induction heating: Place the small alloy cylinder obtained in step 5 into the bottom of a high borosilicate glass test tube, then place the test tube into a conical induction coil and fix it, then turn on the power of the induction coil to heat the small alloy cylinder, so that it is completely melted and drives the bottom of the glass test tube to soften; Step 7, wire drawing: when the bottom of the glass test tube in step 6 is completely softened, use tweezers with an insulating layer to clamp the bottom of the glass test tube, pull out the composite wire material with the alloy liquid completely covered by glass, and quickly cool the composite wire material through cooling water to obtain glass-covered alloy microwires; Step 8: Remove the glass: Use fine sandpaper to gently polish the glass-coated alloy microwire obtained in step 7 to remove the surface glass, and polish it section by section until the glass is completely removed to obtain a superelastic high-temperature shape memory alloy microwire with a temperature above 500°C.
[0042] The large superelastic high-temperature shape memory alloy microwire prepared in this embodiment was subjected to microstructure observation, phase structure analysis, phase transition temperature test and high-temperature superelasticity (stress-strain curve under loading / unloading). The microstructure of the microwire was observed by field emission scanning electron microscope (SEM), and the results showed that the surface was relatively smooth and the diameter of the microwire was about 60 μm. The room temperature phase structure of the microwire was analyzed by X-ray diffractometer (XRD), and the results showed that the microwire was a single structure of tetragonal martensite phase at room temperature. The phase transition temperature of the microwire during the heating and cooling process was measured by differential scanning calorimeter (DSC), and the results showed that the martensite phase transition start temperature, termination temperature, austenite phase transition start temperature and termination temperature of the microwire were all much higher than 100° C., indicating that the microwire belongs to the category of high-temperature shape memory alloy. The stress-strain curve of the microwire during loading and unloading at high temperature was measured by dynamic mechanical property tester (DMA), and the results showed that the microwire had excellent superelasticity at 505° C., the recoverable strain was 10.5%, and the non-recoverable strain was only 0.1%.
[0043] Example 4 The molecular formula of the superelastic high temperature shape memory alloy microwire above 500°C in this embodiment is (Ni 57 Mn 20 Ga 23 ) 99.0 B 0.9 Ce 0.1 .
[0044] This embodiment includes the following steps: Step 1: Melting the master alloy: weigh the elemental Ni and elemental Mn with a mass purity of not less than 99.95% and an atomic ratio of 2:7, and place them in a vacuum suspension melting furnace at a vacuum degree of 4.5×10 -3 Pa, the melting temperature is 1480℃, and after being completely melted, it is kept warm for 8min, and the melting is turned over 3 times to obtain a nickel-manganese master alloy, and then the surface oxide scale is polished off, and the specific composition of the nickel-manganese master alloy is measured, and finally it is cut into small pieces to obtain a small nickel-manganese master alloy; Step 2: Mix the small piece of nickel-manganese master alloy obtained in step 1 with single element Ni, single element Ga, single element B and single element Ce with a purity of not less than 99.95%, according to (Ni 57 Mn 20 Ga 23 ) 99.0 B 0.9 Ce 0.1 batching to obtain a mixed material; Step 3: Melting the master alloy: Place the mixture obtained in step 2 into a vacuum non-consumable arc melting furnace and evacuate the furnace to a pressure of 2.3×10 -3Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and evacuate the furnace for the second time until the pressure in the furnace is 2.3×10 -3 Pa, argon gas is filled again until the pressure in the furnace is -0.05MPa, and finally the titanium ingot is melted to further remove the oxygen in the furnace, with a melting current of 250A~320A, and the melting is turned over for 5 times, wherein electromagnetic stirring is added for 30s~45s during the second, third and fourth melting processes, and vacuum arc melting is performed to obtain a master alloy button ingot; Step 4: Suction casting: Grind the master alloy button ingot obtained in step 3, remove the oxide scale and clean it, then cut it into small pieces and put it into a vacuum arc melting furnace. First, evacuate the furnace to a pressure of 2.3×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, finally melt the titanium ingot to further remove the oxygen in the furnace, and then perform suction casting to obtain an alloy rod with a diameter of 5mm; Step 5: Prepare alloy cylinders: grind and clean the surface of the alloy rod obtained in step 4, and then cut it into small alloy cylinders with a length of 5 mm; Step 6, induction heating: Place the small alloy cylinder obtained in step 5 into the bottom of a high borosilicate glass test tube, then place the test tube into a conical induction coil and fix it, then turn on the power of the induction coil to heat the small alloy cylinder, so that it is completely melted and drives the bottom of the glass test tube to soften; Step 7, wire drawing: when the bottom of the glass test tube in step 6 is completely softened, use tweezers with an insulating layer to clamp the bottom of the glass test tube, pull out the composite wire material with the alloy liquid completely covered by glass, and quickly cool the composite wire material through cooling water to obtain glass-covered alloy microwires; Step 8: Remove the glass: Use fine sandpaper to gently polish the glass-coated alloy microwire obtained in step 7 to remove the surface glass, and polish it section by section until the glass is completely removed to obtain a superelastic high-temperature shape memory alloy microwire with a temperature above 500°C.
[0045] The large superelastic high-temperature shape memory alloy microwire prepared in this embodiment was subjected to microstructure observation, phase structure analysis, phase transition temperature test and high-temperature superelasticity (stress-strain curve under loading / unloading). The microstructure of the microwire was observed by field emission scanning electron microscope (SEM), and the results showed that the surface was relatively smooth and the diameter of the microwire was about 85 μm. The room temperature phase structure of the microwire was analyzed by X-ray diffractometer (XRD), and the results showed that the microwire was a single structure of tetragonal martensite phase at room temperature. The phase transition temperature of the microwire during the heating and cooling process was measured by differential scanning calorimeter (DSC), and the results showed that the martensite phase transition start temperature, termination temperature, austenite phase transition start temperature and termination temperature of the microwire were all much higher than 100° C., indicating that the microwire belongs to the category of high-temperature shape memory alloy. The stress-strain curve of the microwire during loading and unloading at high temperature was measured by dynamic mechanical property tester (DMA), and the results showed that the microwire had excellent superelasticity at 510° C., the recoverable strain was 12.3%, and the non-recoverable strain was only 0.12%.
[0046] Example 5 The molecular formula of the superelastic high temperature shape memory alloy microwire above 500°C in this embodiment is (Ni 57 Mn 24 Ga 19 ) 99.3 B 0.5 Ce 0.2 .
[0047] This embodiment includes the following steps: Step 1: Melting the master alloy: weigh the elemental Ni and elemental Mn with a mass purity of not less than 99.93% and an atomic ratio of 2:6, and place them in a vacuum suspension melting furnace at a vacuum degree of 4×10 -3 Pa, the melting temperature is 1430℃, and after being completely melted, it is kept warm for 12min, and the melting is turned over 3 times to obtain a nickel-manganese master alloy, and then the surface oxide scale is polished off, and the specific composition of the nickel-manganese master alloy is measured, and finally it is cut into small pieces to obtain a small nickel-manganese master alloy; Step 2: Mix the small piece of nickel-manganese master alloy obtained in step 1 with single element Ni, single element Ga, single element B and single element Ce with a purity of not less than 99.93%, according to (Ni 57 Mn 24 Ga 19 ) 99.3 B 0.5 Ce 0.2 batching to obtain a mixed material; Step 3: Melting the master alloy: Place the mixture obtained in step 2 into a vacuum non-consumable arc melting furnace and evacuate the furnace to a pressure of 2×10 -3Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and evacuate the furnace for the second time until the pressure in the furnace is 2×10 -3 Pa, argon gas is filled again until the pressure in the furnace is -0.05MPa, and finally the titanium ingot is melted to further remove the oxygen in the furnace, with a melting current of 250A~320A, and the melting is turned over for 5 times, wherein electromagnetic stirring is added for 30s~45s during the second, third and fourth melting processes, and vacuum arc melting is performed to obtain a master alloy button ingot; Step 4: Suction casting: Grind the master alloy button ingot obtained in step 3, remove the oxide scale and clean it, then cut it into small pieces and put it into a vacuum arc melting furnace. First, evacuate the furnace to a pressure of 2×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and finally melt the titanium ingot to further remove the oxygen in the furnace, and then perform suction casting to obtain an alloy rod with a diameter of 6mm; Step 5: Prepare alloy cylinders: grind and clean the surface of the alloy rod obtained in step 4, and then cut it into small alloy cylinders with a length of 4 mm; Step 6, induction heating: Place the small alloy cylinder obtained in step 5 into the bottom of a high borosilicate glass test tube, then place the test tube into a conical induction coil and fix it, then turn on the power of the induction coil to heat the small alloy cylinder, so that it is completely melted and drives the bottom of the glass test tube to soften; Step 7, wire drawing: when the bottom of the glass test tube in step 6 is completely softened, use tweezers with an insulating layer to clamp the bottom of the glass test tube, pull out the composite wire material with the alloy liquid completely covered by glass, and quickly cool the composite wire material through cooling water to obtain glass-covered alloy microwires; Step 8: Remove the glass: Use fine sandpaper to gently polish the glass-coated alloy microwire obtained in step 7 to remove the surface glass, and polish it section by section until the glass is completely removed to obtain a superelastic high-temperature shape memory alloy microwire with a temperature above 500°C.
[0048] The large superelastic high-temperature shape memory alloy microwire prepared in this embodiment was subjected to microstructure observation, phase structure analysis, phase transition temperature test and high-temperature superelasticity (stress-strain curve under loading / unloading) test. The microstructure of the microwire was observed using a field emission scanning electron microscope (SEM), and the results showed that the surface was relatively smooth and the diameter of the microwire was about 72 μm. The room temperature phase structure of the microwire was analyzed using an X-ray diffractometer (XRD), and the results showed that the microwire had a dual-phase structure at room temperature, including a tetragonal martensite phase and a face-centered cubic precipitation phase. The microwire was observed using a field emission scanning electron microscope (SEM), and the results showed that the microwire had a dual-phase structure at room temperature, including a tetragonal martensite phase and a face-centered cubic precipitation phase. The phase transition temperature of the microwire during the heating and cooling process was measured by a scanning calorimeter (DSC). The results showed that the martensitic phase transformation start temperature, end temperature, austenitic phase transformation start temperature and end temperature of the microwire were all much higher than 100°C, indicating that the microwire belongs to the category of high-temperature shape memory alloys. The stress-strain curve of the microwire during loading and unloading at high temperature was measured by a dynamic mechanical properties tester (DMA). The results showed that the microwire has excellent superelasticity at 520°C, with a recoverable strain of 10.9% and an irrecoverable strain of only 0.15%.
[0049] Example 6 The molecular formula of the superelastic high temperature shape memory alloy microwire above 500°C in this embodiment is (Ni 55 Mn 23 Ga 22 ) 99.31 B 0.6 Ce 0.09 .
[0050] This embodiment includes the following steps: Step 1: Melting the master alloy: weigh the elemental Ni and elemental Mn with a mass purity of not less than 99.95% and an atomic ratio of 2:4, and place them in a vacuum suspension melting furnace at a vacuum degree of 3×10 -3 Pa, the melting temperature is 1440℃, and after being completely melted, it is kept warm for 13min, and the melting is turned over 3 times to obtain a nickel-manganese master alloy, and then the surface oxide scale is polished off, and the specific composition of the nickel-manganese master alloy is measured, and finally it is cut into small pieces to obtain a small nickel-manganese master alloy; Step 2: Mix the small piece of nickel-manganese master alloy obtained in step 1 with single element Ni, single element Ga, single element B and single element Ce with a purity of not less than 99.95%, according to (Ni 55 Mn 23 Ga 22 ) 99.31 B 0.6 Ce 0.09 batching to obtain a mixed material; Step 3: Melting the master alloy: Place the mixture obtained in step 2 into a vacuum non-consumable arc melting furnace and evacuate the furnace to a pressure of 2.7×10 -3Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and evacuate the furnace for the second time until the pressure in the furnace is 2.7×10 -3 Pa, argon gas is filled again until the pressure in the furnace is -0.05MPa, and finally the titanium ingot is melted to further remove the oxygen in the furnace, with a melting current of 250A~320A, and the melting is turned over for 5 times, wherein electromagnetic stirring is added for 30s~45s during the second, third and fourth melting processes, and vacuum arc melting is performed to obtain a master alloy button ingot; Step 4: Suction casting: Grind the master alloy button ingot obtained in step 3 to remove the oxide scale and clean it, then cut it into small pieces and put it into a vacuum arc melting furnace. First, evacuate the furnace to a pressure of 2.7×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, finally melt the titanium ingot to further remove the oxygen in the furnace, and then perform suction casting to obtain an alloy rod with a diameter of 4mm; Step 5: Prepare alloy cylinders: grind and clean the surface of the alloy rod obtained in step 4, and then cut it into small alloy cylinders with a length of 6 mm; Step 6, induction heating: Place the small alloy cylinder obtained in step 5 into the bottom of a high borosilicate glass test tube, then place the test tube into a conical induction coil and fix it, then turn on the power of the induction coil to heat the small alloy cylinder, so that it is completely melted and drives the bottom of the glass test tube to soften; Step 7, wire drawing: when the bottom of the glass test tube in step 6 is completely softened, use tweezers with an insulating layer to clamp the bottom of the glass test tube, pull out the composite wire material with the alloy liquid completely covered by glass, and quickly cool the composite wire material through cooling water to obtain glass-covered alloy microwires; Step 8: Remove the glass: Use fine sandpaper to gently polish the glass-coated alloy microwire obtained in step 7 to remove the surface glass, and polish it section by section until the glass is completely removed to obtain a superelastic high-temperature shape memory alloy microwire with a temperature above 500°C.
[0051] The large superelastic high-temperature shape memory alloy microwire prepared in this embodiment was subjected to microstructure observation, phase structure analysis, phase transition temperature test and high-temperature superelasticity (stress-strain curve under loading / unloading). The microstructure of the microwire was observed by field emission scanning electron microscope (SEM), and the results showed that the surface of the microwire was relatively smooth and the diameter of the microwire was about 72 μm. The room temperature phase structure of the microwire was analyzed by X-ray diffractometer (XRD), and the results showed that the microwire was a single structure of tetragonal martensite phase at room temperature. The phase transition temperature of the microwire during the heating and cooling process was measured by differential scanning calorimeter (DSC), and the results showed that the martensite phase transition start temperature, termination temperature, austenite phase transition start temperature and termination temperature of the microwire were all much higher than 100° C., indicating that the microwire belongs to the category of high-temperature shape memory alloy. The stress-strain curve of the microwire during loading and unloading at high temperature was measured by dynamic mechanical property tester (DMA), and the results showed that the microwire had excellent superelasticity at 510° C., the recoverable strain was 13.2%, and the non-recoverable strain was only 0.16%.
[0052] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A superelastic high temperature shape memory alloy microwire with a temperature above 500°C, characterized in that: The molecular formula of the superelastic high temperature shape memory alloy microwire is: (Ni a Mn b Ga c ) 100-x-y B x Ce y , where a, b, c, x, and y represent the atomic percentage values of the corresponding elements.
2. The superelastic high temperature shape memory alloy microwire with a temperature above 500°C according to claim 1, characterized in that: The (Ni a Mn b Ga c ) 100-x-y B x Ce y In the equation, a is 53~57, b is 20~24, c is 19~23, x is 0.1~0.9, y is 0.05~0.5, and a+b+c=100.
3. The superelastic high temperature shape memory alloy microwire with a temperature above 500°C according to claim 1, characterized in that: The large superelastic high temperature shape memory alloy microwire still has superelasticity at a temperature of 530° C., with a recoverable strain of not less than 9.5% and a non-recoverable strain of not more than 0.1%.
4. A method for preparing a superelastic high temperature shape memory alloy microwire at a temperature above 500°C as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: Step 1, melting the master alloy: weighing single element Ni and single element Mn with an atomic ratio of 2:3-8, and placing them in a vacuum suspension melting furnace for vacuum suspension melting to obtain a nickel-manganese master alloy, then grinding off the surface oxide scale, measuring the specific composition of the nickel-manganese master alloy, and finally cutting them into small pieces to obtain small pieces of nickel-manganese master alloy; Step 2: Mix the small piece of nickel-manganese master alloy obtained in step 1 with single element Ni, single element Ga, single element B and single element Ce according to (Ni a Mn b Ga c ) 100-x-y B x Ce y batching to obtain a mixed material; Step 3, melting the master alloy: placing the mixture obtained in step 2 into a vacuum non-consumable arc melting furnace for vacuum arc melting to obtain a master alloy button ingot; Step 4, suction casting: grinding the oxide scale and cleaning the master alloy button ingot obtained in step 3, then cutting it into small pieces, placing it in a vacuum arc melting furnace for suction casting, and obtaining an alloy rod with a diameter of 4 mm to 6 mm; Step 5: Prepare alloy cylinders: grind and clean the surface of the alloy rod obtained in step 4, and then cut it into small alloy cylinders with a length of 4 mm to 6 mm; Step 6, induction heating: Place the small alloy cylinder obtained in step 5 into the bottom of a high borosilicate glass test tube, then place the test tube into a conical induction coil and fix it, then turn on the power of the induction coil to heat the small alloy cylinder, so that it is completely melted and drives the bottom of the glass test tube to soften; Step 7, wire drawing: when the bottom of the glass test tube in step 6 is completely softened, use tweezers with an insulating layer to clamp the bottom of the glass test tube, pull out the composite wire material with the alloy liquid completely covered by glass, and quickly cool the composite wire material through cooling water to obtain glass-covered alloy microwires; Step 8: Remove the glass: Use fine sandpaper to gently polish the glass-coated alloy microwire obtained in step 7 to remove the surface glass, and polish it section by section until the glass is completely removed to obtain a superelastic high-temperature shape memory alloy microwire with a temperature above 500°C.
5. The method according to claim 4, characterized in that The mass purity of the elemental Ni and elemental Mn described in step 1 and the elemental Ni, elemental Ga, elemental B and elemental Ce described in step 2 is not less than 99.9%.
6. The method according to claim 4, characterized in that During the vacuum suspension melting process described in step 1, the vacuum degree is less than 5×10 -3 Pa, the melting temperature is 1400℃~1500℃, keep warm for 5min~15min after complete melting, and turn over and melt 3 times.
7. The method according to claim 4, characterized in that Before vacuum arc melting in step 3, vacuum is first evacuated to a pressure lower than 3×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and evacuate the furnace for the second time until the pressure in the furnace is less than 3×10 -3 Pa, and then fill with argon again until the pressure in the furnace is -0.05MPa. Finally, the titanium ingot is melted to further remove the oxygen in the furnace.
8. The method according to claim 4, characterized in that During the vacuum arc melting process described in step 3, the melting current is 250A~320A, and the melting is performed 5 times, wherein electromagnetic stirring is added for 30s~45s during the second, third and fourth melting processes.
9. The method according to claim 4, characterized in that Before the suction casting in step 4, vacuum the furnace until the pressure inside is less than 3×10 -3 Pa, then fill with argon until the pressure in the furnace is -0.05MPa, and finally melt the titanium ingot to further remove the oxygen in the furnace.